Trade Unionism and Social Protest Movements in Portuguese Call Centres - Roque, Isabel Maria Bonito (2018)
Since the late 1980s, with the phenomenon of neoliberal globalization and the expansion of the third sector, there was an increase in the proportion of service workers, leading to a decline in the unionization rate. Portuguese trade unionism has been mainly characterized by the absence of a collective organization, not having adapted itself to the evolution of society. Therefore, trade unions face new and hard challenges concerning their organization, strategy of action, social and labor intervention with workers, trying to revive class consciousness lost to individualism. Call centres represent one of the areas which personifies the whole set of technological innovation, being considered as the fastest developing form of e‐work. New social protest movements connected with digital labor have emerged in the Portuguese society, including Precários Inflexíveis, Mayday, Ferve, Precariações, Indignados and more specifically the Call Centre Workers' Trade Union. Between 2008 and 2016, forty semi‐structured and biographical interviews were conducted with former and present call centre workers, trade union delegates and activists from social protest movements. This essay is aimed at analyzing how these “virtual real” social movements organize themselves and have become relevant to the “awakening” of Portuguese call centre workers' class consciousness.